Schools without failure - Glasser, William, 1925- (New York : Perennial Library, 1975)
Presents an examination of the American school system, chronicling its shortcomings proposing the author's view on a new program based on increased involvement, relevance, and thinking.
Includes bibliographical references and index.
Professional
Professional.
Bureche Teacher Resource Library.
Keywords: Education -- United States; Education -- Aims and objectives; Motivation in education; Education -- United States; Education -- Aims and objectives; Motivation (Psychology)